Wybrane aspekty kształtowania się tożsamości człowieka w rodzinie - Sokal, Urszula (Wydawnictwo Naukowe UAM, 2000)
Shaping a child’s identity is a developmental task, in which participate its parents. Together with them, in a modern family, TV plays an important role, which is often a basic source of information and patterns to follow. Contents of TV programs influence one’s identity. That is why parents should know what their children watch. Only then can they strengthen TV’s positive influences and counteract negative ones.
Selected aspects of shaping man’s identity in a family